Type Of Dung Beetle Forest Unila Integrated Conservation Education On Utilization Block In Tahura War - Sigit Prayogi; Bainah Sari Dewi; Yulia Rahma Fitriana; Sugeng P Harianto (University of Lampung, 2023)
Dung beetles are very important decomposer components in secondary forest ecosystems. This dung beetle plays an important role because the beetle has a role in breaking down the feces of various types of animals. This study aims to determine the species diversity of the Dung Beetle in the UNILA HPKT Arboretum in the Tahura War Utilization Block. The tools used in this study were tools such as hoes, traps made of buckets measuring ± 1 liter and containing ± 500 ml of water and plastic cups containing feces, then plastic cups connected to wires, and cameras. The materials used in this study were cow feces, deer feces and goat feces which were still fresh. The method in this study used the trap method. The diversity of dung beetle species in the 3 months of the study found 3 species, namely Catharsius molossus (H' = 0.92), Oryctes rhinoceros (H' = 0.97), and Aphodius marginellus (H' = 1.01). The suggestion from this study is that the results of the study show that the diversity of dung beetles in Tahura WAR in the utilization block is relatively low because of the low vegetation cover and food sources.